2021
DOI: 10.13057/biodiv/d220759
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Gracilaria species (Gracilariales, Rhodophyta) obtained from the South Coast of Java Island, Indonesia

Abstract: Abstract. Meinita MDN, Akromah N, Andriyani N, Setijanto, Harwanto D, Liu T. 2021. Molecular identification of Gracilaria species (Gracilariales, Rhodophyta) obtained from the South Coast of Java Island, Indonesia. Biodiversitas 22: 3046-3056. The study of seaweeds diversity and species identification is an important component of marine resource management. However, seaweed identification based on morphological characteristics has several limitations. Besides, DNA barcodes or the partial sequences of cytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…G. edulis and G. salicornia were earlier discovered on the south coast of Yogyakarta, i.e., on Drini Beach and Kukup Beach, respectively (Romdoni et al 2018;Meinita et al 2021). Following previous research, the same species was discovered in the same location in the current investigation.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…G. edulis and G. salicornia were earlier discovered on the south coast of Yogyakarta, i.e., on Drini Beach and Kukup Beach, respectively (Romdoni et al 2018;Meinita et al 2021). Following previous research, the same species was discovered in the same location in the current investigation.…”
supporting
confidence: 75%
“…in Indonesia have been reported molecularly and morphologically, including G. edulis, G. salicornia, G. verrucosa, G. gigas, G. textorii, G. firma, G. gracilis, G. vermiculophyla, G. babae, G. isabellana, G. damaecornis, and G. yoneshigueana in Drini Beach in Yogyakarta, Kondang Merak in East Java, South Sulawesi, Kukup Beach in Yogyakarta, Nusakambangan Beach in Central Java, Karapyak Beach in West Java, Menganti Beach in Central Java, and Serangan Island in Bali, respectively (Romdoni et al 2018;Arbit et al 2019;Meinita et al 2021;Wirawan et al 2021). Gracilaria spp.…”
mentioning
confidence: 99%
“…Previous studies have shown that Indonesia produces the highest macroalgae in biomass culture in Southeast Asia, surpassing the Philippines (Hurtado et al, 2019;Rimmer et al, 2021). Another study also stated that 555 seaweed species are found in Indonesia, and 55 of them have high economic value, such as Gracilaria and Euchema (Meinita et al, 2021). As the primary producer in the coastal ecosystem, macroalgae are not a plant but an informal group of protists (Eliáš, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The use of molecular markers is important to clarify the study of the morphology and genetic quality of a species. The use of rbcL gene sequences has been recorded in various studies, showing that these marker genes are quite potential and useful for studying genetic variation in natural populations (Lim et al, 2013;Djakatara et al, 2018;Annisaqois et al, 2018;Ratnawati et al, 2020;Meinita et al, 2021;Wirawan et al, 2021;Hamdan et al, 2013). Previous studies were still limited so we started to do DNA info and barcodes red algae in the Ternate Island Sea.…”
Section: Introductionmentioning
confidence: 99%